On the Multimetal - Multiligand Complex Formation Equilibria of Adenine and Histidine - Verma, Shalini; Kumar Srivastava, Bipin; Rani, Nidhi; Krishna, V. (International Journal of Engineering and Technology, 2018)
Quaternary metal chelates of Cu (II), Co (II), Cd (II), Pb (II), Zn (II) and Ni (II) metal ions with Adenine and L-Histidine have been studied by Potentiometric technique at 0.1 M NaNO3 ionic strength under biologically relevant condition in aqueous medium. Formation of quaternary species along with hydroxyl, protonated, binary and ternary species has been reported. The percentage of species formation of different systems was determined through SCOGS computer program by utilizing titration values of ternary and quaternary systems. The obtained species percentage was shown through graphs plotted between species and solution pH. The distribution of species at different pH was sketched out through ORIGIN 6.1. The order of stability constants of quaternary system has been calculated. Speciation curves of all the quaternary system under studied show that complexation takes place simultaneously.Â Â